2000
DOI: 10.1177/09500170022118536
|View full text |Cite
|
Sign up to set email alerts
|

The Myth of the Urban Peasant

Abstract: This paper explores, the `myth of the urban peasant', the widespread belief that urban Russian households are surviving the collapse of employment and money incomes by turning to subsistence agriculture. On the basis of the analysis of official and survey data the paper shows that although many urban households grow food in their garden plots, those with low money incomes are the least likely to do so, while subsistence production is a complement rather than an alternative to paid employment. Moreover, those w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Some of the most striking findings came out of the household survey that we carried out in 1998, which gave us high-quality quantitative data on which to test various hypotheses. One of these, suggested by Lena Varshavskaya of Kemerovo, was that domestic agriculture did not provide the lifeline for the poor that many commentators claimed because the costs of domestic agriculture in time and money far outweighed the returns in agricultural produce, but rather it was a leisure activity of the better off that exemplified the Soviet work ethic, idealisation of nature and traditions of exchange (Clarke et al 2000). Another very significant finding was that of the dominance of institutional over market determinants of wage differentiation, strongly supportive of the traditional, although largely forgotten, argument of industrial relations specialists against labour economists and, in a similar vein, of the complete inability of labour economics to explain the domestic division of paid and unpaid labour.…”
Section: Sarah Ashwinmentioning
confidence: 99%
“…Some of the most striking findings came out of the household survey that we carried out in 1998, which gave us high-quality quantitative data on which to test various hypotheses. One of these, suggested by Lena Varshavskaya of Kemerovo, was that domestic agriculture did not provide the lifeline for the poor that many commentators claimed because the costs of domestic agriculture in time and money far outweighed the returns in agricultural produce, but rather it was a leisure activity of the better off that exemplified the Soviet work ethic, idealisation of nature and traditions of exchange (Clarke et al 2000). Another very significant finding was that of the dominance of institutional over market determinants of wage differentiation, strongly supportive of the traditional, although largely forgotten, argument of industrial relations specialists against labour economists and, in a similar vein, of the complete inability of labour economics to explain the domestic division of paid and unpaid labour.…”
Section: Sarah Ashwinmentioning
confidence: 99%
“…Second, the diversity of motivations for FSP beyond simple economic or cultural impetuses is recognised. Clarke et al (2000) argued that FSP was rather a leisure activity than a coping strategy even in Russia during the transition in the 1990s while at the same time being an important source of food for a large part of the population. Sharashkin (2008) reported almost equal importance among four motives for FSP: auxiliary source of food, connection to nature, hobby/recreation and time spent with other people, all being identified as important by 70%-77% of respondents in his survey in the Vladimir region in Russia.…”
Section: Fsp As Hobby and Source Of Good Foodmentioning
confidence: 99%
“…Researchers challenged claims that urban agriculture offered survival to those too poor to participate in postsocialist economies. They showed that those who grew food continued to rely on market produce, while those at the very bottom of the economic scale possessed neither skills, tools, nor time to produce sustenance themselves (Clarke et al 2000 ). Instead, vegetables from urban plots were understood as pathways to boosting meagre incomes (Round et al 2010 ); accessing community mutual aid (Czegledy 2002 ); or restoring one’s sense of dignity and preparedness (Hervouet 2003 ; Zavisca 2003 ; Ries 2009 ).…”
Section: A Narrative Approach To Motives For Urban Agriculturementioning
confidence: 99%